2020
DOI: 10.1017/s0014479720000125
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of a long-term conservation agriculture experiment in Malawi and lessons for future experimental design

Abstract: Resilient cropping systems are required to achieve food security in the presence of climate change, and so several long-term conservation agriculture (CA) trials have been established in southern Africa – one of them at the Chitedze Agriculture Research Station in Malawi in 2007. The present study focused on a longitudinal analysis of 10 years of data from the trial to better understand the joint effects of variations between the seasons and particular contrasts among treatments on yield of maize. Of further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…The CA treatments lead to an increased grain yield, resulting in a significantly higher yield of proteins and Se, had no effect on the yield of K, Mg, Mn, P, and Zn, and reduced yield of Fe. Our results on grain yield agree with many previous reports that showed that CA maize yields outperformed conventional practise ( 53 58 ). In this study, a higher yield increase was obtained, with 14.8–33% in 2018–29 and 21.7–75.2% in 2019–20 (excludingT2).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The CA treatments lead to an increased grain yield, resulting in a significantly higher yield of proteins and Se, had no effect on the yield of K, Mg, Mn, P, and Zn, and reduced yield of Fe. Our results on grain yield agree with many previous reports that showed that CA maize yields outperformed conventional practise ( 53 58 ). In this study, a higher yield increase was obtained, with 14.8–33% in 2018–29 and 21.7–75.2% in 2019–20 (excludingT2).…”
Section: Resultssupporting
confidence: 92%
“…Similar disparities in different years of agronomic trials have been reported in different research stations of Malawi ( 64 ). Previous studies have also shown that rainfall and drought during cropping season can influence maize physiological response and agronomic performance under CA conditions ( 32 , 35 , 53 ). A longitudinal analysis of the long-term CA experiment in Malawi showed a season effect on yield, and highlighted the strong interaction between CA treatments and climatic conditions ( 53 ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The design of the experiment was therefore informed by a power analysis to detect a 10% effect. This is a novel approach to agronomic biofortification studies; typically, studies on maize (and other crops) have limited replication and therefore limited power to detect small effect sizes (Button et al., 2013; Lark et al., 2020; Uttley, 2019). A second objective is to determine how the effectiveness of agronomic biofortification will differ between Lixisols and Vertisols, with maize grown on Vertisols expected to have higher baseline grain Zn concentrations (Chilimba et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Composite samples from each treatment (about 5 cobs) were taken for dry cob weight, grain weight, and grain moisture at harvest. Samples were sundried, and grain moisture content was measured and adjusted to 13% using a handheld grain moisture meter (Dickey-John USA Grain Moisture Tester, Minigac GAC 2500_US, R. K. Enterprises, New Delhi, India) as stipulated in Lark et al [37]. The grain moisture adjustment was performed to help standardise the yield performance of different treatments and eliminate experimental error sources due to differences in drying methods.…”
Section: Weed Managementmentioning
confidence: 99%